Estudio de la situación socioeconómica y académica del docente de la Facultad de Medicina de la Universidad Peruana Cayetano Heredia. - PAMO REYNA, Oscar; RUIZ DIAZ, Jorge E (Revista Médica Herediana, 2013)
One hundred and twenty one teachers, 51.3% of the total of the faculty of medicine Alberto Hurtado of UPCH were surveyed in order to determine some social, economic and academia characteristics. We found: age average, 49.4 yr;89.3% male; 87.6% were married; 85.8% lived in middle and high social level areas; average of children 2.8; 8.3% were full-time teachers; average of years in teaching 19.5 yr; 95.9% were attracted for teaching; 85.1% would not abandon teaching; 42.4% were satisfied; 52.9% had training in teaching methods; 54.5% were doing research; 55.9% had published; 90.0% belong to the Ministry of Health-Hospitals; 79.2% do private practice; 75.0% own a house; 52.5% had other member of their family working and 72.5% had private practice as the main income. We concluded that our teaching staff belongs in average, to the middle class, do teaching as an extra activity, have interest and experience in teaching but do not have enough pedagogical education and that research and publications could increase.